INDIKASI MANAJEMEN LABA MELALUI AKRUAL DISKRESIONER PADA PERUSAHAAN TELEKOMUNIKASI DI BURSA EFEK INDONESIA - Khaiyat, M Dinul (JURNAL AKUNTANSI, 2016)
This study aimed to determine whether there is an indication of earnings management through discretionary accruals in telecomunication companies on the Indonesia Stock Exchange.           The sample used for this study were seven telecomunications company that listed on the indonesia stock exchange for three years, from 2012 until 2014. Using descriptive quntitative method with documentation data collecting, this study will disclose the fact of telecomunication companies earnings management by manager. Earnings management is measured using a proxy discretionary accruals (DA), which is calculated using a modified Jones model.            Based on the evidence gathered in financial reports, the maximum value of DA is 0,5742 and the minumum value is -0,5317. The result of this study is DA of telecomunication companies has positive and negative value. This means, there is an indication of earnings management in financial statement of telecomunication companies for three years, from 2012 until 2014.Keywords: Earnings Management and Discretionary Accruals